2015
DOI: 10.1111/jace.13490
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Molten B2O3, B2O3–SiO2, Na2O–B2O3, and Na2O–SiO2 Systems

Abstract: systems was measured along with their temperature and composition. It was observed that the thermal conductivity of pure B 2 O 3 increased with temperature, until about 1400 K, and then decreased subsequently. Using the MAS-NMR, 3Q-MAS, and Raman spectroscopy, the structure of B 2 O 3 and SiO 2 in the B 2 O 3 -SiO 2 system was confirmed. Findings show that an addition of B 2 O 3 into the pure SiO 2 system causes a significant decrease in thermal conductivity, due to the formation of boroxol rings. The thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 54 publications
2
26
0
Order By: Relevance
“…Owing to the modification of the transient hot‐wire method, the thermal conductivity has been successfully measured in various molten oxide systems at high temperature . Several studies have revealed that the thermal conductivity of the molten oxide system is closely related to the network structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the modification of the transient hot‐wire method, the thermal conductivity has been successfully measured in various molten oxide systems at high temperature . Several studies have revealed that the thermal conductivity of the molten oxide system is closely related to the network structure.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates the basic oxide behavior of FeO x . Recently, Kim and Morita determined the linear relationship between the thermal conductivity and the Q 4 units (tetrahedral silicon associated with four bridging oxygen atoms), in the molten Na 2 O–SiO 2 system. This implies the significant role of the silicate network on the thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, above the Debye temperature, owing to the approximately constant specific heat capacity (C) and mean particle velocity (v), the thermal conductivity of the oxide system decreases with increasing temperature as a result of the decrease in the phonon mean free path of collision (l), which is proportional to the inverse of the temperature (1/T). [25][26][27][28][29]31] Hence, it can be inferred that thermal conductivity reaches the maximum value around the Debye temperature, and then it decreases with higher temperatures. Therefore, identifying the Debye temperature in the oxide system is essential to evaluate the temperature at which thermal conductivity shows the maximum and to determine which variables mainly affect the thermal conductivity at the given temperature.…”
Section: Consideration Of One-dimensional Debye Temperature (θ D1 )mentioning
confidence: 98%
“…Although understanding the thermal conductivity of the molten oxide is also important for the thermal processing of the glass [22], the thermal conductivity measurement in the molten oxide system has been limited because of the large convection and the radiation effects [23]. However, owing to the several modifications of the non-steady state method, the thermal conductivity has been successfully measured in the molten oxide system over the last few decades [24][25][26][27][28][29][30][31][32][33]. Similar to other physical properties of the molten oxide system, the thermal conductivity is closely related to the network structure (i.e., silicate, aluminate, and borate structure.)…”
Section: Introductionmentioning
confidence: 99%